Turbidity removal from surface water and landfill leachate using cactus opuntia - Yin, Chun Yang; Suhaimi, Abdul Talib; Lim, Ying Pei; Mohd. Safirun Nizan, Ismail; Siti Nor Aisah, Abd- Razak; Ahmad Mahyuddin, Mohd. Mohtar (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/